Cannabisin D from Sinomenium Acutum Inhibits Proliferation and Migration of Glioblastoma Cells through MAPKs Signaling. (31st December 2021) - Zhang, Dianbao; Li, Chunhe; Zhang, Luting; Li, Bo; Wang, Yu; Wang, Rui; Chen, Zaixing; Xu, Liang; Liu, Tao
Abstract: Glioblastoma is the most common and malignant tumor in human central nervous system with poor prognosis. From the dried stem of Sinomenium acutum, an herbal medicine, five compounds (sinomenine, syringin, corchoionoside C, protocatechuic acid and cannabisin D) were isolated, characterized and subjected to cytotoxicity screening on U-87 and U-251 glioblastoma cells. Cannabisin D presented effective inhibitory effects on the proliferation and migration of glioblastoma cells. By flow cytometry, real-time PCR and Western blotting, cell apoptosis and cell cycle arrest were proved to contribute to the anti-glioblastoma effects. Further, the activation of MAPKs signaling (p38 MAPK, p42/p44 MAPK and SAPK/JNK) was observed in glioblastoma cells upon cannabisin D treatment by Western blotting, indicating the involvement of MAPKs signaling in the inhibitory effects of cannabisin D. These data suggested that S. acutum is a novel natural source of cannabisin D and cannabisin D is a novel anti-glioblastoma agent candidate.